Genotypic and metabolic phenotype changes in breast cells using gold‐based compound cancer treatment - Yu, Richard Ming Chuan (2018)
Breast cancer incidence rate remains very high, being one of the top deadly diseases in women around the world. Survival rate has increased in recent years due to modern advanced technologies capable of detecting this disease earlier. However, in the treatment area, researchers are still trying to get new effective chemotherapeutic compounds for breast cancers. Existing popular anticancer platinum‐based compounds cause resistance and a decreased response rate. In addition, they are less effective in advanced breast cancers. Recent findings highlighted that cancer stem cells are the root of cancer that causes cancers, and its recurrence after remission to certain years (5 years in average) followed by treatments. This re‐emerging of cancer stem cell theory also triggered researchers to find new effective metal‐based compounds for cancer stem cells and advanced breast cancers. The aim of this research is to measure genotype and metabolic phenotype changes of breast cancer cells upon treated with novel gold‐based 3F series compounds in order to prove the hypothesis that these novel gold‐based compounds are less toxic and have better inhibition against the growth of breast cancer cells compared to platinum‐based compounds. Thus, in this research, the novel gold‐based 3F series compounds such as 3F1: Triphenylphosphanegold (I) O‐methyl‐N‐ (3‐ fluorophenyl) thiocarbamate, 3F2: Tricyclohexylphosphanegold (I) O‐methyl‐N (3‐flurophenyl) thiocarbamate, 3F3: Bis (diphenylphosphinoferrocene) di gold (I) O‐methyl‐N‐ (3‐fluorophenyl) thiocarbamate and 3FL: O‐methyl‐N‐ (3‐ fluorophenyl) thiocarbamate were used in vitro experiments with human breast cancer cell lines (MDA‐MB‐231 & MCF‐7), human primary breast cancer cells (in‐house cultured) and human breast cancer stem cells (parental breast cancer stem cell & breast cancer stem cell). Canine mammary tumor cell (CMT‐stylo) was also used in the assessment of the selected gold compound. Cytotoxicity assay, real‐time cell analysis (RTCA), apoptosis, caspase 3/7 activity assays and cell cycle assays were done followed by phenotypic microarrays and microRNA expression profile experiments. The novel compound 3F1 was found to be less toxic and effective against breast cancer cells such as MDA‐MB‐231, MCF‐7 cells, primary breast cancer cells (BCA) and breast cancer stem cells (BCSC‐P & BCSC). The IC50 dose of the novel 3F1 compound against those breast cancer cells was approximately 6 times lower than that of cisplatin (CDDP). This meant the novel gold‐based 3F1 compound is 6 times stronger anticancer properties than cisplatin. The compound 3F1 induced caspase 3/7 dependent apoptosis and affected cell cycle arrest at both “S”and “G2/M”phases. Furthermore, significant downregulation of commonly upregulated miR‐155 of breast cancers was observed in all the tested breast cancer cells: MDA‐MB‐231, MCF‐7, BCA (primary breast cancer cells), BCSC‐P (parental breast cancer stem cells) and BCSC (breast cancer stem cells) which were treated with respective IC50 dose of the novel gold compound 3F1 except in the canine mammary tumor cells (CMT‐stylo). Last but not the least, the high‐throughput modern technology, Phenotypic Microarrays for mammalian cells system (PM‐M) was used for identifying reproducible metabolic phenotypic profile of the breast cancer cells, MDA‐MB‐231 cells. Overall PMM results indicated that the novel gold‐based compound 3F1 caused significant metabolic shifts in the treated MDA‐MB‐231 cell in terms of markedly reduction of utilizing energy substrates compared to the non‐treated MDAMB‐ 231, control samples. Arginine and arginine containing dipeptides were found to be prominent energy sources in the treated breast cancer cells. All in all, findings from this research are beneficial not only in breast cancer therapeutic drug development but they can also be applied to translational medicines in the field of diagnosis, prognosis, prediction and ultimately towards targeted curative rather than palliative treatments for breast cancers.